Do vazio ao objeto: das Ding e a sublimação em Jacques Lacan - Ariana Lucero (2010)
The dissertation intends to investigate the concept of sublimation on the work of Jacques Lacan, from the paradigmatic definition formulated in his Seminar 7: "the sublimation raises an object to the dignity of the Thing" (LACAN, 1997 [1959-60], p. 112). Thus follows, firstly, an approach of the notion of das Ding, or the Thing, from Freuds Project for a Scientific Psychology (1895) to its Lacanian developments, in which the French psychoanalyst relates das Ding to the Real. Secondly, the Lacanian critique of Freuds idea that sublimation involves a shift in drives aim is examined. As for Lacan drive has no natural pre-existing aim, every drive activity would be sublimatory if we were to embrace Freuds definition. Lacan, then, purposes his own concept of sublimation focusing on the relations between the later and the notion of object. Finally, we aim to demonstrate, from Lacans analysis of courtly love literature and some works of art that the refered Lacanian concept of sublimation consists in the explicitation of the empty proper to the sphere of the Real, through the use of Symbolic and Imaginary resources.